Investigation of athletes’ attitudes towards nationalism in sports - Dağgül, Şevval; Sadik, Reşat (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study was conducted to determine the attitudes of athletes towards nationalism in sports. In this study, the survey model was utilized. The sample consisted of students from the Faculty of Sports Sciences at Düzce University (n=545; 364 male and 181 female), including national athletes, university students, and athletes engaged in individual and team sports. The Nationalism Attitude Scale in Sports was used for data collection. The scale consists of 18 items in total, 9 under negative nationalism, 7 enthusiastic nationalisms, and 2 under constructive nationalism, divided into a total of 3 sub dimensions. Since the obtained data showed a normal distribution, parametric tests were employed. According to the results, it was determined that the nationalist attitudes of the athletes were at a moderate level and that there was a significant difference in the negative nationalism dimension in terms of age variable, national status and the departments they studied in (p<0.05), and that there was no significant difference in other variables (p>0.05). Overall, athletes’ attitudes toward nationalism in sports were at an adequate and desirable level, with differences observed only in the negative nationalism sub-dimension.